2019
DOI: 10.3847/1538-4357/ab17d5
|View full text |Cite
|
Sign up to set email alerts
|

3D Radiation Hydrodynamics of a Dynamical Torus

Abstract: We have developed a new dynamical model of the torus region in active galactic nucleus (AGN), using a three-dimensional radiation hydrodynamics algorithm. These new simulations have the specific aim to explore the role of radiatively-driven outflows, which is hotly debated in current literature as a possible explanation for the observed infrared emission from the polar regions of AGN. In this first paper, we only consider radiative effects induced by the primary radiation from the AGN. The simulations generate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 55 publications
2
36
0
Order By: Relevance
“…Gas being swept up in a region that becomes self-obscured to the AGN radiation will have less momentum deposited, giving rise to a "failed wind". Such mass fallback has been seen in radiationhydrodynamic simulations (e.g Wada 2012; Williamson et al 2019), with observational evidence also found in low-velocity molecular outflow components of the Ciricnus galaxy . Gas presence in this fall-back region is transitional, probably of lower column density, and the lack of direct AGN radiation makes the region dark in the IR.…”
Section: The Dark Fall-back Regionsupporting
confidence: 61%
See 1 more Smart Citation
“…Gas being swept up in a region that becomes self-obscured to the AGN radiation will have less momentum deposited, giving rise to a "failed wind". Such mass fallback has been seen in radiationhydrodynamic simulations (e.g Wada 2012; Williamson et al 2019), with observational evidence also found in low-velocity molecular outflow components of the Ciricnus galaxy . Gas presence in this fall-back region is transitional, probably of lower column density, and the lack of direct AGN radiation makes the region dark in the IR.…”
Section: The Dark Fall-back Regionsupporting
confidence: 61%
“…Pier & Krolik 1992;Fabian et al 2009;) and RHD simulations confirm it for both single dusty clumps as well as massive dusty molecular disks (e.g. Dorodnitsyn et al 2011;Schartmann et al 2011;Wada 2012;Namekata et al 2014;Namekata, & Umemura 2016;Chan & Krolik 2017;Williamson et al 2019). Such radiation pressure driving is most effective for regions with τ V ∼ 1.…”
Section: Physical Conditions Of the Dusty Molecular Gasmentioning
confidence: 86%
“…Proga et al 2000), with recent studies also involving dusty winds (e.g. Dorodnistyn et al 2016;Chan & Krolik 2017;Williamson et al 2019). The existence of dust within warm absorbers has been reported (e.g.…”
Section: Introductionmentioning
confidence: 81%
“…Netzer 1987;Matthews et al 2017). In addition, the geometry of the flow in line-driven and dust-driven winds is also sensitive to the SED anisotropy Williamson et al 2019) and motivates further work involving multi-frequency radiation hy- drodynamics. Unlike M16, we do not have an emissivity profile with radius along the disc midplane, and all photon packets are launched from the central source.…”
Section: Kinematics Geometry and Input Sedmentioning
confidence: 94%